Languages, identities and intercultural communication in South Africa and beyond - Kaschula, Russell (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"African countries and South Africa in particular, being multilingual and multicultural societies, make for exciting sociolinguistic and applied language analysis in order to tease out the complex relationship between language and identity. Sociolinguistic theory as well as critical language awareness and translanguaging with its many facets will be applied in this book to various communicative scenarios, both on the continent and in South Africa in an accessible and practical way. Africa lends itself to such sociolinguistic analysis concerning language, identity and intercultural communication. This book reflects consciously on the North-South debate and the need for us to create our own ways of interpretation emanating from the South and speaking back to the North and to issues that pertain to the South, including southern Africa. Aspects such as language and power, language planning, policy and implementation, culture, prejudice, social interaction, translanguaging, intercultural communication, education, gender, and auto ethnography are covered in this book. A valuable resource for students studying in African Sociolinguistics, Language and Identity and Applied Language Studies. Also, anyone interested in the relationship between language and society on the African continent would find the book to be easily accessible"--
Language policies, identities and African nations: 'Language checks and balances' -- Languages, identities, politics and power: 'Speaking back to power' -- Languages, dialects, identities and varieties: 'Tower of Babel: Speaking in tongues' -- Languages, identities and cultures: 'What's orange for you is red for me' -- Linguistic prejudice and identities: 'To speak or not to speak?' -- Languages, identities and gender: 'Wathint' umfazi wathint' imbokodo -- You strike a woman; you strike a rock!' -- Languages, identities, power, multilingualism and education: 'Thetha, bua, khuluma, speak: your language or mine?' -- Intercultural communication, identities and the workplace: 'A smile is a smile in any language' -- Languages, identities and protest in creative contexts: The Trevor Noah effect: 'Born a Crime' -- Languages and identities: A personal journey: 'Umntu ngumntu ngabantu -- a person exists by virtue of others' -- Conclusion. 'Phela-phela ngantsomi, our story is done'.
Keywords: Anthropological linguistics -- South Africa; Multilingualism -- South Africa; Language policy -- South Africa; Language planning -- South Africa; FOREIGN LANGUAGE STUDY / African Languages; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Journalism